Geographic Location: A Value Variation Factors of Intangible Asset - Sani Inusa Milala; Khadijah Md Ariffin; Rozilah Kasim; Narimah Kasim; Azlina Md Yassin; Mohd Hafizal Ishak (International Journal of Scientific Research and Innovative Studies, 2022)
It was ascertained that all the development on this earth is linked to the land either directly or indirectly, the location where the constituent of intangible asset exists has an indirect effect on the market value of the intangible asset, It has been noticed that individuals construct their asset without giving careful thought to the link among geographic location and asset market values. Considerable importance is attached in the modernity has given rise to the idea of asset location, which has an impact on the usage and worth of asset. The worldwide engagement in innovation and growth prospects as a way of achieving economic continued success by focusing on site still hasn't been widely used or publicly acknowledged because factors such as intangible assets are the constituent of the business, this study has the primary aim of exploring the influence of the geographic location factor on intangible asset value variation, the study employed the intensive review of literature method. It was found that the location factor has an influence on the intangible asset value directly or indirectly and it was concluded that location also mediates the influence of location on the variation of intangible asset value.